Multimedia Speech Therapy Tools and Other Disability Solutions as Part of a Digital Ecosystem Framework - Calder, David (Springer, 2010)
Curtin University has developed a multimedia prototype system for use by speech therapists to assist in the rehabilitation of motor speech impaired patients. These are often stroke victims who have to relearn the ability to communicate effectively. The process is usually laborious and instead of the usual card-based prompts used by the therapist, this multimedia solution offers screen and audio prompts together with high quality digitised speech. The result is a reduced work load for the therapist. In parallel with this work, is a Mobility Aid Assistive Device Program for the visually impaired. The support clusters for all these groups, whether they be therapists, caregivers, manufacturers of hardware or software do not interact to the extent they might. The author proposes a collaborative digital ecosystem framework that would assist this challenge.